2011
DOI: 10.1093/hmg/ddr045
|View full text |Cite
|
Sign up to set email alerts
|

Ataxin-2 intermediate-length polyglutamine expansions in European ALS patients

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal adult-onset neurodegenerative disease primarily affecting motor neurons. We recently identified intermediate-length polyglutamine (polyQ) expansions (27-33 Qs) in ataxin 2 as a genetic risk factor for sporadic ALS in North American ALS patients. To extend these findings, we assessed the ataxin 2 polyQ repeat length in 1294 European ALS patients and 679 matched healthy controls. We observed a significant association between polyQ expansions and ALS (>30 Qs; P= 6.2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
101
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(109 citation statements)
references
References 33 publications
7
101
0
1
Order By: Relevance
“…The polyQ-expansion of ATXN2 leads to a process of protein insolubility and aggregate formation with insidious toxicity throughout the nervous system, depending on the expansion size and polygenic interactions, possibly also on CAA-interruptions within the CAG-repeat. Neurodegenerative processes known as Spino-cerebellar Ataxia type 2 (SCA2), the motor neuron degeneration Amyotrophic Lateral Sclerosis (ALS13), Frontotemporal dementia, Supranuclear palsy, or Levodopa-responsive Parkinsonism can be triggered by this mechanism (32)(33)(34)(35)(36)(37)(38)(39). In Drosophila melanogaster flies, the Ataxin-2 ortholog dATX2 was shown to act as a generic modifier gene that affects multiple if not all neurodegenerative disorders (40).…”
mentioning
confidence: 99%
“…The polyQ-expansion of ATXN2 leads to a process of protein insolubility and aggregate formation with insidious toxicity throughout the nervous system, depending on the expansion size and polygenic interactions, possibly also on CAA-interruptions within the CAG-repeat. Neurodegenerative processes known as Spino-cerebellar Ataxia type 2 (SCA2), the motor neuron degeneration Amyotrophic Lateral Sclerosis (ALS13), Frontotemporal dementia, Supranuclear palsy, or Levodopa-responsive Parkinsonism can be triggered by this mechanism (32)(33)(34)(35)(36)(37)(38)(39). In Drosophila melanogaster flies, the Ataxin-2 ortholog dATX2 was shown to act as a generic modifier gene that affects multiple if not all neurodegenerative disorders (40).…”
mentioning
confidence: 99%
“…The association of ALS with ataxin‐2 longer normal alleles was confirmed in familial and sporadic ALS in different populations: North American, Dutch‐Belgian, Italian, French‐Canadian, Chinese, and Turkish. Lee et al did not find association of ALS with long repeats in other polyglutamine disease genes 86. In a meta‐analysis, which included 7505 controls and 6151 sporadic ALS patients from different geographical and ethnic origins, Neuenschwander et al found that alleles up to 30 repeats do not increase apparent risk.…”
Section: Atxn2 and Amyotrophic Lateral Sclerosis (Als)mentioning
confidence: 99%
“…The CAG repeats are translated into long stretches of glutamine, and while normal individuals have <22 glutamines, patients with spinocerebellar ataxia type 2 harbor >33 [32]. Intermediate length ataxin-2 repeats-between 22 and 33 glutamine residues-are associated with an enhanced risk of developing ALS [34,35]. Ataxin-2 directly interacts with TDP43, and intermediate-length ataxin-2 polyglutamine repeats facilitate this association and promote incorporation of TDP43 into cytoplasmic stress granules.…”
Section: Alternative Rna-based Mechanismsmentioning
confidence: 99%
“…Supporting the connection between abnormal RNA processing and motor neuron disease, nonsense or missense mutations in FUS, EWSR1, and TAF15 are associated with fALS [30,31]. Moreover, trinucleotide (CAG) expansion mutations in ATXN2, encoding the RNA-binding protein ataxin-2, cause spinocerebellar ataxia or ALS, depending on the number of CAG repeats [32][33][34][35], and, in some populations, hexanucleotide (G 4 C 2 ) expansion mutations in the noncoding region of the C9orf72 locus account for up to 40 % of fALS [17,18]. Individuals carrying C9orf72 expansion mutations also exhibit RNA-rich nuclear foci, indicative of fundamental abnormalities in RNA metabolism.…”
Section: Introductionmentioning
confidence: 99%